Peran Pendamping Lokal Desa Dalam Pelaksanaan Program Pembangunan Dan Pemberdayaan Masyarakat di Desa Kedai Durian Kabupaten Deli Serdang - Pebri Amelinda (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2022)
The limitations of villages in various sectors make villages the main focus of the government in proposing community empowerment and village development programs. The current situation in Kedai Durian village shows that there is still a lack of community empowerment; it can be seen from the low level of community independence, and developments that have not hit the target point. The purpose of this study was to determine the role of the Village Local Facilitator (PLD) in assisting the Kedai Durian village in implementing village development programs and community empowerment. The theory used in this study is the theory of empowerment, where community empowerment is the main focus of the government to achieve the goal of creating an independent and empowered village. This research method uses a qualitative research method with a descriptive approach with the number of informants 7 people namely the Village Head, PLD, and 5 Warg with data collection techniques through interview and observation methods. The data analysis technique in this study refers to 3 flow of activities, namely data reduction, data presentation, and drawing conclusions. The results of research in Kedai Durian village related to the role of Village Local Facilitators in the implementation of development and community empowerment programs in Kedai Durian village Deli Serdang district are quite good, this can be seen by the implementation of development and empowerment programs run by Local Village Facilitators and the community well.